Development of complex technology of strengthening of thin-walled cutting tools - Skoblo, T.S.; Romaniuk, S.P.; Sidashenko, A.I.; Taran, V.S.; Nezovibat’ko, Yu.N.; Pilgui, N.N. (Вопросы атомной науки и техники, 2016)
The complex technology to strengthen thin-walled cutting tools by coating for a long, stable operation of disk
knives has been proposed. The cutting tools for crushing nuts used in the confectionery industry made of cold-rolled
steel sheet of 65 G and X20Cr13 types were used for coatings application. Two methods of cleaning and
strengthening of such tools were proposed and investigated: ion bombardment with titanium ions (PVD) and
vacuum-arc method using RF-discharge (RF). The structure and chemical composition of knifes with TiN coating
were investigated using scanning electron microscopy and X-ray microanalysis. A new way to strengthen thin disk
knives with TiN nanocoating was patented in Ukraine. Предложена комплексная технология упрочнения тонкостенного режущего инструмента с помощью
покрытий для обеспечения более длительной стабильной работы дисковых ножей. Покрытия наносили на
режущий инструмент, изготовленный из холоднокатаной тонколистовой стали 65Г и 20Х13, для дробления
орехов в кондитерском производстве. Предложены и исследованы два метода очистки и упрочнения таких
инструментов: ионная бомбардировка ионами титана и вакуумно-дуговой метод с использованием ВЧ-
разряда. Исследованы структура и химический состав ножей с покрытием TiN с помощью сканирующей
электронной микроскопии и микрорентгеноспектрального анализа. Новый способ упрочнения тонкостенных
дисковых ножей нанопокрытиями TiN защищён патентом Украины. Запропоновано комплексну технологію зміцнення тонкостінного ріжучого інструмента з допомогою
покриттів для забезпечення більш тривалої стабільної роботи дискових ножів. Покриття наносили на
ріжучий інструмент, виготовлений з холоднокатаної тонколистової сталі 65Г і 20Х13, для подрібнення
горіхів в кондитерському виробництві. Запропоновано та досліджено два методи очищення і зміцнення
таких інструментів: іонне бомбардування іонами титану і вакуумно-дуговий метод з використанням ВЧ-
розряду. Досліджено структуру та хімічний склад ножів з покриттям TiN за допомогою скануючої
електронної мікроскопії та мікрорентгеноспектрального аналізу. Новий спосіб зміцнення тонкостінних
дискових ножів нанопокриттям TiN захищений патентом України.